(untitled) (Baghdad Science Journal, 2011)
Crystalline In2O3 Thin films have been prepared by flash evaporation. We have studied the crystal structure of as deposited at 303K and annealed at 523K using X-ray diffraction. The Hall Effect measurements confirmed that electrons were predominant charges in the conduction process (i.e n-type).It is found that the absorption coefficient of the prepared films decreases with increasing Ta. The d.c conductivity study showed that the conductivity increase with increasing Ta , whereas the activation energy decreases with increasing Ta. Also we study the barrier tunneling diode for In2O3/Si heterostructure grown by Flash evaporation technique. (capacitance-voltage C-V) spectroscopy measurements were performed at 303 K and at the annealing temperature 523K. The built in voltage has been determined and it depends strongly on the annealing process of the heterojunction. From all above measurements we assumed an energy band diagram for In2O3 /Si(P-type) heterojunction.